A Política Externa Independente em revista: de como ocorre a impressão definitiva da dimensão africana na política externa brasileira - Leite, Fernando Sousa (Temporalidades, 2016)
O presente artigo objetiva identificar a inserção do componente africano no âmbito da Política Externa Independente (1961-64) como resultado da influência do pensamento de Gilberto Freyre, interpretado como uma raiz esquecida da PEI que continua a fundamentar o discurso brasileiro hodierno quando da inflexão diplomática em direção à África. ABSTRACT: This article aims to present the bases of Brazil s Independent Foreign Policy (1961-64) as being influenced by Gilberto Freyre s thinking, as well by his concepts, especially in what concerns the diplomatic movement towards Africa observed in that period and that still sustains its roots in the contemporary Brazilian foreign affairs. Furthermore, it objectives to elucidate how the Brazil s Independent Foreign Policy included the African dimension into Brazilian external relations. KEYWORDS: Brazil independent foreign policy; African approchement; Gilberto Freyre.